2014
DOI: 10.17562/pb-50-10
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Fingerprint Recognition Using Artificial Neural Networks

Abstract: How to citeComplete issue More information about this article Journal's homepage in redalyc.org Scientific Information System Network of Scientific Journals from Latin America, the Caribbean, Spain and Portugal Non-profit academic project, developed under the open access initiative  Abstract-This paper presents an implementation of Artificial Neural Networks (ANN) for acoustic fingerprints recognition, applied to the identification of marine vessels. In many cases, the vessel recognition process from an audib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…We found that many of these works have focused on geometric approaches and intelligent passive sensor arrays configuration to efficiently cover large and neuralgic areas [15,16]. Likewise, localization processes have been developed using pattern recognition methods such as game theory and artificial neural networks [17][18][19]. However, this type of approach requires constant feedback from implementation experiences to provide better results.…”
Section: Introductionmentioning
confidence: 99%
“…We found that many of these works have focused on geometric approaches and intelligent passive sensor arrays configuration to efficiently cover large and neuralgic areas [15,16]. Likewise, localization processes have been developed using pattern recognition methods such as game theory and artificial neural networks [17][18][19]. However, this type of approach requires constant feedback from implementation experiences to provide better results.…”
Section: Introductionmentioning
confidence: 99%